Toward a socially-distributed mode of knowledge production: framing the contribution of lay people to scientific research. (30th July 2021) - Palumbo, Rocco; Manna, Rosalba; Douglas, Alexander
Lay people involvement is arising as a viable alternative to conventional modes of knowledge generation and dissemination. However, little is known about the roles that lay people may play in scientific research; moreover, management and organisational challenges characterise the implementation of a socially-distributed mode of knowledge production. To shed light into this issue, we performed a realist literature review that involved 81 papers. The study findings suggested that lay people may variously contribute in knowledge co-production; their role depends on the degree of autonomy they have and on the type of relationship they establish with expert scientists. The propensity of expert scientists and lay people to bring diverging inputs in knowledge co-production should be acknowledged and carefully addressed, in order to avoid drawbacks on the knowledge production ability of research institutions. The outcomes of citizen science projects should be assessed from both an economic and a societal point of view.